The effectiveness of promotional efforts by Malay Mail to increase readership / Nurul Asyuhada Kassim - Kassim, Nurul Asyuhada (Faculty of Business and Management, 2005)
This research was conducted to identify whether the promotional efforts implemented by Malay Mail is effective or not, in order to enhanced public awareness towards its promotional efforts. The main objective of this research is to know the level of public awareness towards the company's existing promotional efforts. The respondent of this study consist of Malay Mail readers located in Klang Valley especially in Kuala Lumpur and Petaling Jaya areas. 100 questionnaires had been distributed randomly to those respondents who read Malay Mail. The conclusion of this study is the outcome from the survey analysis and findings. Through the research, it shows that more than half of their readers are aware about Malay Mail promotional efforts since they are participated and exposed to the activity.